Online forums and the enlargement of public space - Tsaliki, Liza (Javnost (Ljubljana), 2002)
This paper has focused on online political forums as newly emerged public spaces that contribute to the enhancement of public deliberation. Its aim has been to study the deliberative feature of the Internet and assess the extent to which ordinary citizens contribute to the political process through public debate online. The main research question is concerned with the way in which the Internet facilitates participation in politics, enables democratic deliberation, and provides a forum for reasoned argumentation. The extent to which this occurs has been studied through the content analysis of open publicforums in Greece, the Netherlands and Britain. Research findings show a high level of interactive communication, high degree of search for information, diversity of opinions and publics and a moderate degree of substantiated argumentation- indicating an enlargement of public space in principle. However, the analysis stresses that unless netizens test their opinions in public systematically, the notion of the Internet as a tool for democratic deliberation is seriously undermined and runs the risk of being replaced by a push-button democracy. In that respect, cyberspace resembles the familiar world of everyday politics as an arena for the ongoing struggle for power and influence, despite the hype surrounding it.
Keywords: javnost; komuniciranje; communication; informacije; politics; politika; democracy; demokracija; računalniške komunikacije